BUKTI EFISIENSI BANK SYARIAH DI INDONESIA DAN MALAYSIA: ROA, BANK SIZE DAN NPF - Wardana, Guntur Kusuma; Abdani, Fadlil (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
The study aims to determine the efficiency level of Islamic Commercial Banks in Indonesia and Malaysia, as well as the effect of Return on Assets (ROA), Bank size and Non-Performing Financing (NPF) on the efficiency of Islamic Commercial Banks in Indonesia and Malaysia for the 2015-2020 period by using Tobit regression test. The type of research carried out is quantitative research with a descriptive approach. Purposive sampling is a sampling method used in this study with a sample of 5 Islamic Commercial Banks in Indonesia and Malaysia. The results of the study indicate that all Islamic Commercial Banks in Indonesia during the study period were efficient as a whole in the research sample as many as 3 Islamic Commercial Banks, while the National Khazanah Bank of Malaysia, there were Islamic banks that were still not efficient as many as one Islamic bank and one other bank the results were efficient. The results of the Tobit regression test state that the ROA and NPF variables have a significant effect on efficiency. In contrast, Bank size has no significant effect on efficiency.